2007
DOI: 10.1258/026835507780807211
|View full text |Cite
|
Sign up to set email alerts
|

Local metabolic, pathophysiological and histological changes in venous ulcers

Abstract: Differences in levels of venous blood gases and anaerobic metabolites indicate a potential difference in the causation and development of superficial versus deep venous caused ulcers. This may have clinical significance for the diagnosis and treatment of these conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 13 publications
0
7
0
1
Order By: Relevance
“…7,14 The blood flow bypasses the capillaries, which leads to an impaired transcapillary metabolism, microcirculatory dysfunction, and the subsequent development of trophic ulcers. 25 The results of this study showed that there was no statistically significant difference between C4 and C5/C6 CEAP classes in terms of superficial and perforator venous reflux parameters. This study would suggest that none of the developmental theories of trophic ulcers find their full hemodynamic confirmation.…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…7,14 The blood flow bypasses the capillaries, which leads to an impaired transcapillary metabolism, microcirculatory dysfunction, and the subsequent development of trophic ulcers. 25 The results of this study showed that there was no statistically significant difference between C4 and C5/C6 CEAP classes in terms of superficial and perforator venous reflux parameters. This study would suggest that none of the developmental theories of trophic ulcers find their full hemodynamic confirmation.…”
Section: Discussionmentioning
confidence: 59%
“…7,14 The blood flow bypasses the capillaries, which leads to an impaired transcapillary metabolism, microcirculatory dysfunction, and the subsequent development of trophic ulcers. 25…”
Section: Discussionmentioning
confidence: 99%
“…The values of lactate and gas analysis before and after the treatment with semi synthetic diosmin were not significantly changed in the samples of venous blood, even after the static load (Table 5). For patients with C5-6 EpsAspPr the signs of hyperoxemia were found, and a local increase of lactate and pyruvate levels occurred at the static load 8,18 . Thus, for patients with C5-6 EpsAspPr stage of HVI the levels of partial pressure and oxygen saturation were decreased, while the levels of carbon dioxide and bicarbonates were increased, and the values of lactate and pyruvate were not significantly changed.…”
Section: The Resultsmentioning
confidence: 99%
“…HVI was diagnosed on the left leg (26), right leg (36) or bilaterally (18). The youngest patient was 36, and the oldest 84 years old (X+ SD = 52.3+10.5).…”
Section: The Resultsmentioning
confidence: 99%
“…2123 Many theories have been proposed but none has provided an entirely satisfactory, complete and coherent explanation of the events observed at histopathological, cellular, molecular and biochemical levels. 7,2427…”
Section: Aetiologymentioning
confidence: 99%